Morphologic Changes in Contralateral Lumbar Foramen in Unilateral Cantilever Transforaminal Lumbar Interbody Fusion Using Kidney-type Intervertebral Spacers. Issue 5 (June 2015) - Iwata, Takahiro; Miyamoto, Kei; Hioki, Akira; Fushimi, Kazunari; Ohno, Takatoshi; Shimizu, Katsuji
<x xml:space="preserve">Abstract</x> Study Design: A retrospective study of 58 patients undergoing cantilever transforaminal lumbar interbody fusion (c-TLIF). Objectives: To evaluate morphologic changes in the intervertebral foramen (IVF) on the side contralateral to spacer insertion in patients undergoing c-TLIF using plain x-ray films and computed tomography scan. Summary of Background Data: The morphologic changes in the contralateral lumbar foramen in c-TLIF using unilateral insertion of spacers have not been well studied. Materials and Methods: Fifty-eight consecutive patients with lumbar dysplastic changes or degenerative disk diseases underwent c-TLIF using 96 kidney-type spacers with local bone grafts. Radiographic findings (sagittal disk angle), computed tomography scan findings (coronal disk angle, disk height, foraminal height (FH), foraminal width, and cross-sectional area of IVF in contralateral lumbar foramen) were compared between preoperative period and 6 months after surgery. The correlations between contralateral lumbar foraminal dimensions and disk height, sagittal disk angle, and coronal disk angle were analyzed. Results: After c-TLIF, sagittal angle, disk height, FH, foraminal width, and cross-sectional area of the IVF were significantly increased. Increase in posterior disk height showed a positive correlation with increases in FH, foraminal width, and cross-sectional area of IVF (r=0.235–0.511). However, the increase in sagittal disk angle showed a negative correlation with changes in foraminal width and cross-sectional area of IVF (r=–0.256 to –0.206). Conclusions: Lumbar foraminal dimensions on the side contralateral to spacer insertion increased significantly after c-TLIF, suggesting that c-TLIF enables indirect decompression of the contralateral nerve root. Although increase in posterior disk height was shown to be an important factor to increase contralateral foraminal size, segmental lordosis was a risk factor for a decrease in contralateral foraminal size.